Behavioral Differences Towards Internal and External Factors in Making the Bid/No Bid Decision - Bageis, Abdulrahman; Falqi, Ibrahim I.; Alshehri, Abdullah; Alsulamy, Saleh; Alsahli, Tariq A. (Civil Engineering Journal, 2019)
Decision-making and subjective evaluation are two important aspects that characterizes the involvement of an organization in tender process. Moreover, selection of the right project to bid for is a principal feature of business success. The study aims to investigate the behavioral differences of Saudi construction contractors toward internal and external factors based on the process of modelling the bidding decisions. A quantitative research design is used to investigate the behavioral differences of 97 contractors recruited from construction industry of Saudi Arabia. A questionnaire was distributed among the respondents that would help in identifying the significant level of factors affecting the bid or no bid decision. The impact of internal and external factors on the bidding decisions was evaluated using one-way ANOVA analysis. The results have shown a significant and positive effect of internal and external factors on the bid or no bid decision; including job start time, work capital requirement, availability of qualified human resources, bidding methods, bidding document price, project supervision procedure and etc. The study has helped in establishing a better understanding toward the behavioral differences of contractors with respect to the bidding decisions.